Caught between HIV exceptionalism and health service integration: Making visible the role of public health policy in the scale-up of novel sexual health services. (November 2021) - Gómez-Ramírez, Oralia; MacKinnon, Kinnon R.; Bannar-Martin, Sophie; Karlsson, Maja; Haag, Devon; Worthington, Catherine; Gilbert, Mark; Grace, Daniel
Abstract: The role of contextual factors for program implementation is well-documented; however, their changing function throughout implementation phases is less established. We conducted an institutional ethnography to understand how structural conditions for scaling up initiatives are shaped by public health policy. We conducted 25 interviews with implementers of a comprehensive sexual health testing service in Canada, 21 meeting observations, and textual analyses of key policies and reports. Our analysis revealed a disjuncture between implementers' task of scaling up programming and the actualities of working within the discursive and material confines of policies premised on HIV exceptionalism and underfunded integrated health services. Highlights: We examined how policy context shapes the scale-up of novel sexual health services. Regional scale-up efforts were shaped by policy premised on HIV exceptionalism. Implementers' work necessitated equitable funding for comprehensive testing. Competing policies structure conditions for scale-up during program implementation. Attention to changing macro-level factors which shape health services is required.